Book Review: Screen Workers and the Irish Film Industry (Denis Murphy: Liverpool University Press, 2024) - Tracy, Tony (Irish Journal of Arts Management and Cultural Policy, 2025)
In Screen Workers and the Irish Film Industry, Denis Murphy analyses the history of the screen industries in Ireland and the part played by labour relations. Drawing on official records, interviews and using previously unused records from the trade union archives and other labour history sources, this is a chronological history of the growth of the Irish screen industries. While the emphasis is on film and television workers, the book acknowledges the essential producer contribution to building the industry as it exists today. However, it also emphasises producer obligations towards the screen workers they employ and the evolving role of trade unions in the industry. The volume covers both Northern Ireland and the Republic of Ireland.